O1-S02.05 Population based surveillance for cervical intraepithelial neoplasia grade 3 and adenocarcinoma in situ in three central cancer registries, USA 2009. (10th July 2011) - Flagg, E W; Datta, S Deblina; Lyu, C; Nagaraja, J; Copeland, G; Silva, W; Peters, E; Cole, L; Tucker, T; Byrne, M J; Unger, E R; Saraiya, M; et al.
Abstract : Background: Human papillomavirus (HPV) vaccine has been recommended routinely to 11–12-year-old US girls for cervical cancer prevention since 2006, and evaluation of the population impact of HPV vaccine is a critical need. In addition to measuring the impact of HPV vaccines on cervical cancer incidence, surveillance should include endpoints more proximal in time to HPV infection such as cervical intraepithelial neoplasia grade 3 (CIN3) and adenocarcinoma in situ (AIS). These immediate precursors to invasive cervical cancer manifest only 5–10 years after HPV infection. Although CIN3/AIS are detected during cervical cancer screening, these lesions are not routinely reported to US central cancer registries (CCRs). Compared to other precursor lesions, CIN3/AIS show the most consistent inter-pathologist agreement in histopathology interpretation making them the most suitable precursor lesion surveillance endpoints. Methods: The Centers for Disease Control and Prevention conducted a project in three statewide CCRs to assess the feasibility of collecting data on CIN3/AIS lesions using existing registry infrastructure, a standardised case definition, and well-defined coding rules. State-specific vintage 2009 bridged-race postcensal population estimates were used to calculate incidence rates. Results: Statewide age-adjusted incidence rates of CIN3/AIS in 2009, using the 2000 US Standard Population, were 76.8 (Kentucky), 57.5 (Michigan), and 54.7 (Louisiana) per 100 000 women. Highest rates were observed in those aged 20 to 29; rates among these women were 272.8 in Kentucky, 196.7 in Louisiana, and 192.6 in Michigan. Race was missing for 16% of records. Among records for which race was reported, incidence rates in Kentucky were highest for whites, while rates in Michigan were highest for blacks; in Louisiana rates did not differ significantly between whites and blacks. In each state, overall rates of CIN3/AIS were over sixfold higher than invasive cervical cancer rates. Only 3.8% of cervical lesions were AIS. Conclusions: These results are the first reports of statewide population based incidence of CIN3/AIS in the US, and demonstrate that routine collection of CIN3/AIS lesions by cancer registries is feasible and could provide an earlier endpoint than cervical cancer with which to evaluate the impact of HPV vaccination in the US. Sentinel registries should be established to collect ongoing data on CIN3/AIS to monitor the impact of HPV vaccine in the US.